Laser interferometric measurement of machine tools - Rónai, László; Lénárt, József (Design of Machines and Structures, 2024)
This paper deals with a positioning accuracy measurement on a machine tool to perform calibration. The principle of laser interferometric measurement is introduced, a Renishaw XL-80 laser interferometer is applied to perform measurements. The method-ology of using the system is presented through a practical measurement. The deviations in certain positions are determined, thus the pitch error table of the machine tool can be re-freshed. Thereafter a test running is performed in order to check the accuracy of the ma-chining centre.